YAYOI KUSAMA DAN NARASI FEMINIST ART KARYA SENINYA//NARASI FEMINIST ART PADA KARYA YAYOI KUSAMA - Ainur Khafifah (Kusa Lawa, 2021)
This article is a literacy study of the development of the subject into an object: Yayoi Kusama in the development of his art and how his cultural background, race and gender identity and his body values lead him to the flow of feminist arts which is usually published by each curator and critic on themes. his work. This paper uses a psychoanalytic approach in identifying objects and tendencies that Kusama has brought along in his career. How the charm and existence of Kusama bring along the goals of feminist thought itself, this is one of the feminist thought tools accepted by the audience without having to present upheaval by various people, art is a container of thought that can be accepted by society widely and clearly both from in terms of aesthetics and in terms of value.